2011
DOI: 10.1080/17533015.2010.481288
|View full text |Cite
|
Sign up to set email alerts
|

Cultural activities and public health: research in Norway and Sweden. An overview

Abstract: In Norway and Sweden, the governments see a potential for establishing a policy for cultural participation, based on the assumption that cultural activities will improve health and well-being. Aim: The aim was to survey the scientific literature in Norway and Sweden concerning cultural interventions for increased well-being and health. All applications of cultural activities in medical and leisure time field were included. Methods: Medline, were included. Results: Mostly effects of cultural participation in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 65 publications
1
26
1
4
Order By: Relevance
“…Regarding cultural activities, employees have largely been bystanders (Theorell, Hartzell, & Näslund, 2009). A review of the research completed in Norway and Sweden within cultural activities and health indicates that cultural interventions may promote health and well-being at the population level (Cuypers et al, 2011). A recent prospective study of a representative sample of working Swedes showed an inverse relationship, after 2 years of follow-up, between the frequency of cultural activities with emotional exhaustion (Theorell et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Regarding cultural activities, employees have largely been bystanders (Theorell, Hartzell, & Näslund, 2009). A review of the research completed in Norway and Sweden within cultural activities and health indicates that cultural interventions may promote health and well-being at the population level (Cuypers et al, 2011). A recent prospective study of a representative sample of working Swedes showed an inverse relationship, after 2 years of follow-up, between the frequency of cultural activities with emotional exhaustion (Theorell et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Although there is growing evidence that cultural activities in general may promote health (Cuypers et al 2011; Cox et al 2010; Clift et al 2009; Bygren et al 1996) there are many unanswered questions regarding possibly beneficial health effects of cultural activities organised through work. In a random trial Bygren et al (2009a) have shown that an offer of a cultural activity (self-selected from a list of possible activities) once a week for medical staff lasting for 2 months may have beneficial effects on mental health during this period.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that using music, literature, performance, drama and the visual arts has had demonstrable positive therapeutic outcomes; this applies to both physical and mental health problems (NEF 2009;White 2009;Spandler et al 2007;Staricoff 2004;Stickley 2010;RSPH 2013;Wolf and Wolf 2011;ACE 2012;Jensen 2013). This research also shows an application of not only art participation but also access to arts and culture in a variety of health care settings in Britain, Ireland, Australia, Canada, Norway, Sweden, Brazil, Peru, Finland, the Republic of Lithuania and the United States (Sonke et al 2009;Wikoff 2004;White 2009;ACI 2010;Likanen 2010;Cuypers et al 2011;Parkinson and White 2013;Tellnes 2009;Austin 2014). The positive outcomes from these initiatives have supported developing trends over the past two decades of using the arts in the wider health sector.…”
Section: Background and Contextmentioning
confidence: 95%
“…The division of responsibilities at the political level makes it difficult to develop initiatives concerning culture and health with a formalized coordinated cross-party effort. Furthermore, it is currently difficult to find any evidence, at any of the three levels, suggesting that there are initiatives researching the correlation between an individual's health and participation in cultural experiences as there are in Sweden and Norway (Cuypers et al 2011(Cuypers et al , 2012.…”
Section: Health Promotion and Policy-makingmentioning
confidence: 95%